Synthesis, luminescence properties, and growth mechanisms of YF3:Yb3+/Er3+ nanoplates. Issue 39 (15th September 2015) - Murali, G.; Lee, Byeong Hoon; Mishra, R. K.; Lee, Jae Myeong; Nam, Sang-Hwan; Suh, Yung Doug; Lim, Dong-Kwon; Lee, Joong Hee; Lee, Seung Hee
Abstract : Anisotropically structured upconversion nanocrystal is a promising new class of high performance optical materials. Abstract : Anisotropically structured upconversion nanocrystals capable of exhibiting bright upconversion emission properties are a promising new class of high performance optical materials. In this study, we investigate a facile synthetic method for the new nanoplate structure of YF3 :Yb 3+ /Er 3+ with enhanced luminescence intensity. The shape of YF3 :Yb 3+ /Er 3+ nanocrystals can be controlled by changing the synthesis conditions of the NaOH concentration, reaction time, and surfactant. The concentration of NaOH determines the final structure of YF3 :Yb 3+ /Er 3+ . By increasing the NaOH concentration from 0.25 mmol to 2.5 mmol, YF3 :Yb 3+ /Er 3+ nanoplates transform into NaYF4 :Yb 3+ /Er 3+ nanoparticles; in the absence of NaOH, the nanoplate structure of YF3 :Yb 3+ /Er 3+ changes to particles. The YF3 :Yb 3+ /Er 3+ nanoplates show luminescence efficiency much greater than that of the spherical YF3 :Yb 3+ /Er 3+ nanocrystals.